Effect of a plant extract of fenugreek (Trigonella foenum-graecum) on testosterone in blood plasma and saliva in a double blind randomized controlled intervention study - Lee-Ødegård, Sindre; Gundersen, Thomas E.; Drevon, Christian A. (PLOS ONE, 2024)
Many aging men experience reduced energy and libido related to non-optimal testosterone levels. We conducted a randomized double-blind trial with TrigozimR fenugreek extract to assess impact on plasma and saliva testosterone, and some subjective effects. 95 men (40-80y) completed a 12-week intervention, taking 3 tablets daily with 0 mg (placebo; n = 22), 600 mg (n = 21), 1200 mg (n = 25) and1800 mg (n = 27) fenugreek extract and essential nutrients. Samples were collected at weeks 0, 2, 6, and 12. Participants answered a pre- and post-intervention questionnaire on lifestyle and libido. We measured total testosterone (HPLC-MS/MS) and sex hormone binding globulin (ELISA), calculated free testosterone index (FTI), and measured saliva testosterone. Plasma total testosterone and FTI increased after any dose of TrigozimR vs. baseline (13.0%, p = 1.0x10-4 and 16.3%, p = 6.2x10-6), but not vs. placebo (9.0%, p = 0.122 and 11.3% p = 0.059). 1800 mg TrigozimR resulted in 12.2% increased FTI (p = 0.025). Saliva testosterone concentration increased after any dose of TrigozimR vs. baseline (31.1%, p = 2.3x10-4) and vs. placebo (37.2%, p = 0.042). 1800 mg TrigozimR for 12 weeks resulted in 19.6% (p = 0.006) increased saliva testosterone. Compliance was confirmed by enhanced plasma concentration of 25-hydroxy vitamin D3. We observed no subjective effects or side-effects of TrigozimR. TrigozimR increased saliva and plasma testosterone concentration during intervention but only for saliva vs. placebo. Saliva may be preferred for measuring free testosterone due to no protein-bound testosterone.